Teacher-Student Interactions and Science Classroom Learning Environments in India - Koul, Rekha B. (Curtin University, 2003)
The research reported in this thesis is an in-depth study of teacher-student interactions and science classroom learning environments in Jammu, India. Jammu city is the winter capital of the state of Jammu and Kashmir, situated at the extreme north of India. This is the first time that any learning environment research has been conducted and reported from this part of the world. The objective of this research was to provide further validation information about two already existing learning environment instruments with Indian students and describe, discuss and analyse information on the associations between student’s perceptions of learning environment and their attitudes and cognitive achievements. Differences in the perceptions of different groups namely gender, religious and cultural were also investigated. The present study commenced with a more positivistic framework, with an aim of providing a large-scale quantitative overview. The Questionnaire on Teacher Interaction (QTI), the What is Happening in this Class? (WIHIC) and an Attitude Scale were administered to 1,021 students from 32 science classes in seven different co-educational private schools in Jammu. The data were analysed to determine the reliability, validity and mean of each scale. Students were interviewed to determine further the reliability of the questionnaires, in addition to providing information that might explain the QTI and WIHIC mean scale scores. As a result of critical reflection, the study moved towards a more interpretative framework, drawing on elements of the constructivist and critical theory paradigms. Multiple research methods were used to member and deepen the researchers understanding of the learning environments in Jammu. An educational critique was used to describe the social and cultural factors that could influence the prevailing learning environments.